2014
DOI: 10.1159/000358255
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Combined Application of Magnesium and MK-801 on Analgesic Action of Morphine

Abstract: As previously reported, magnesium ions (Mg2+) administered in relatively low doses markedly potentiated opioid analgesia in neuropathic pain, in which the effectiveness of opioids is limited. Considering that Mg2+ behaves like an N-methyl-D-aspartate receptor antagonist, the effect of this ion on the analgesic action of morphine was compared with that of MK-801. Acute pain was evoked by mechanical or thermal stimuli, whereas neuropathic hyperalgesia was induced by strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Some data indicate that PAG stimulation was effective in mechanical allodynia in the animal model of neuropathic pain [50]. As shown in our previous studies [25,51], the gradual development of mechanical hyperalgesia was observed in STZtreated animals (data not shown). We demonstrated a lack of antinociceptive effect upon MRF application alone over 7 consecutive days in animals with persistent neuropathic pain.…”
Section: Discussionsupporting
confidence: 54%
“…Some data indicate that PAG stimulation was effective in mechanical allodynia in the animal model of neuropathic pain [50]. As shown in our previous studies [25,51], the gradual development of mechanical hyperalgesia was observed in STZtreated animals (data not shown). We demonstrated a lack of antinociceptive effect upon MRF application alone over 7 consecutive days in animals with persistent neuropathic pain.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported to potentiate lidocaine [1], induce analgesia during spinal anesthesia [2,3], improve morphine analgesia in animals [4]and humans [5], and reduce postoperative morphine consumption [6,7]. Several trials with different doses, routes, and methods of administration of magnesium have been reported, some with conflicting results [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that activation of NMDA receptors has important role in the development of morphine tolerance and dependence( 30 ). It has been shown that NMDA receptor antagonist such as MK-801 could prevent morphine-induced tolerance and dependence( 31 ). In this regard, a recent investigation by Zhou et al .…”
Section: Discussionmentioning
confidence: 99%